ANALYZING THE RELATION BETWEEN THE E-COMMERCE DEVELOPMENT AND SMALL MEDIUM ENTERPRISE IN MANADO - Tulung, Jenifer Claudya; Lapian, S.L.H.V. Joyce; Rumokoy, Farlane S (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Nowadays, the development of e-commerce business or online trading in Indonesia has increased d in recent years. The emergence of e-commerce began to create a list of top-down services. Awareness of SMEs in Manado to take advantage of e-commerce already exists and continues to increase. The phenomenon of many SME businesses in Manado using e-commerce in marketing their products is a good sign. The purpose of this research is to know the relationship between e-commerce development of small and medium business in Manado and to reveal the problems faced by Small and Medium Enterprises in using e-commerce in Manado. This research was conducted in Manado as a developing city in Indonesia with small and medium enterprises that use e-commerce and who do not use E-commerce. Qualitative research is deployed and uses explosive research to determine the nature of Small and Medium Enterprises in Manado. The results of this study indicate that e-commerce can increase sales, income, and the number of SMEs customers in Manado. Through E-commerce products that sell and handle SMEs can be better known to people quickly. However, the problem facing SMEs in the use of ecommerce is the lack of knowledge about accessing the ecommerce system and the time limitations of SMEs actors. From the results of this study then there should be attention from the government to conduct socialization or holding a seminar to increase knowledge about ecommerce to the perpetrators SMEs Manado.  Keywords: small medium enterprise, ecommerce impact and its benefit, problem in using ecommerce